LncRNA LINC00944 Promotes Tumorigenesis but Suppresses Akt Phosphorylation in Renal Cell Carcinoma - Chen, Chiheng; Zheng, Hanxiong (Frontiers in Molecular Biosciences, 2021)
Long non-coding RNA (lncRNA) is a kind of RNA that possesses longer than 200 nucleotides and lacks protein coding function. It was recognized as a junk sequence for a long time. Recent studies have found that lncRNAs are actively functioning in almost every aspect of cell biology and involved in a variety of biological functions. LncRNAs are closely related to a variety of human diseases, especially tumors. Recently, lncRNAs are being increasingly reported in renal cancer. In our study, we identified the expression of lncRNA LINC00944 is significantly elevated in renal cell carcinoma (RCC) tissues and cell lines and high LINC00944 expression is significantly correlated with the tumor stage and prognosis of RCC. The knockdown of LINC00944 by CRISPR/dCas9-KRAB in higher expressing 786-O and 769-P RCC cells could significantly decrease proliferation and migration and also promote phosphorylation of Akt compared with the control group. Our study is the first to report the function of lncRNA LINC00944 in RCC. And we provide clinicopathological and experimental evidence that lncRNA LINC00944 acts as an oncogene in RCC, suggesting that targeting lncRNA LINC00944 expression might be a promising therapeutic strategy for the treatment of RCC.